USING STRUCTURAL EQUATION MODELLING (SEM) TO CONSTRUCT THE MODEL FOR CULTIVATING EMPLOYEE EXCELLENCE THROUGH ENGAGEMENT, ENABLEMENT, AND EMPOWERMENT - Iman Permana (FIRM Journal of Management Studies, 2021)
This study quantitatively assessed the model of Employee Excellence with predictor constructs of Employee Engagement, Enablement, and Empowerment.  The analyses utilized Structural Equation Modelling (SEM) with latent variables.  The measurement model for the predictor variables used formative indicators, therefore, this study used Partial Least Square (PLS)-SEM.  The research focused on eight manufacturing companies in Indonesia, with foremen as the unit of analysis, totaling as many as 257 respondents.  Research findings revealed that each predictor construct has a key driver: Psychological Capital was found to be the key driver of Employee Engagement, Infrastructure for Data Sharing (which was later reconfirmed as Knowledge Management) was the key driver of Employee Enablement, and Transformational Leadership was the key driver of Employee Empowerment.  The study also revealed that Employee Engagement, Enablement, and Empowerment altogether related positively and significantly with Employee Excellence.  The research findings provide empirical basis for prioritizing strategic actions on the most important factors for affecting employee engagement, enablement, and empowerment, in order to foster employee excellence.